Patterns of Uveitis in the Middle East and Europe - Ebrahim M Nashtaei; Masoud Soheilian; Carl P Herbort; Mehdi Yaseri (Journal of Ophthalmic & Vision Research, 2011)
Purpose: To compare the patterns of uveitis, emphasizing similarities and discrepancies, in the Middle East and Europe. Methods: Six articles reporting uveitis patterns from the Middle East including a total of 2,693 cases, and seven articles with a sum of 4,379 cases from Europe were analyzed and patterns in each region were defined and compared. Results: In both regions, uveitis was most commonly seen in the fourth decade of life with anterior uveitis being the most common anatomical form. Idiopathic cases accounted for the majority of anterior and intermediate uveitis; toxoplasmosis was the most frequent entity in posterior uveitis while Behcet′s disease and idiopathic forms were the next most common causes in the Middle East and in Europe, respectively. Conclusion: Since patterns of uveitis differ in various geographic regions, discovering these patterns would be helpful for the diagnosis and treatment of this broad category of conditions. This necessitates applying a universal diagnostic classification system to enable accurate comparisons.